(untitled) (Journal of Organizational Psychology, 2018)
This paper explores the cultural values of the displaced Syrian people as they flee their war-torn country. The analysis provides insight into a unique refugee population that now reaches into the millions. It also provides implications for organizations that must assimilate this displaced group into their workforces consisting of different national and organizational cultures. The cultural assessment was conducted using the 5-D Hofstede model of cultural values. It compared the cultural orientations of the Syrian diaspora with those in the countries where the displaced people may eventually settle, as well as Germany, which has already accepted many Syrian refugees. The assessment also contrasts the current findings on Syria with those originally obtained by Hofstede in 1980. The results of this study indicate that integration of the refugees may be difficult. Suggestions for managing the displaced Syrian diaspora are discussed.